SIZE COMPOSITION AND GROWTH RATES OF BLUE KING CRAB PARALITHODES PLATYPUS BRANDT, 1850 IN THE RUSSIAN SECTOR OF THE BERING SEA - P. A. Fedotov; I. S. Chernienko (Известия ТИНРО, 2019)
Size composition and growth rate of blue king crab males are analyzed on the data of 8 bottom trawl surveys conducted in the western Bering Sea in summer-fall seasons within the period from 2005 to 2017. Significant changes in size structure of this population are revealed. Portion of commercial males was the lowest (18.7 %) in 2010 because of the strong yearclass appeared in the catches in 2005, when its males carapace had the width 20–40 mm, that provided in 2008–2010 the percentage of juveniles with the size < 100 mm about 59–60 %. Then this strong year-class reached the commercial size, so the portion of commercial males increased to 66 % in 2014 and to 85 % in 2015–2016. The portion of juveniles was extremely small (3.1–6.5 %) in these years. The portion of commercial males had reduced again to 67 % in 2017 because of a new strong year-class appearance that provided the juveniles percentage increasing to 24.6 %. The mean size of commercial males has increased since 2012 in 18 mm and reached the value of 160.4 mm in 2017. Age of the crab males entry into the commercial cohort is estimated as 8 years. The observed cyclic changes in size composition of blue king crab and estimated value of its growth rate indicate indirectly a good and stable state of its population in the western Bering Sea.